A escola na empresa: considerações sobre a formação do trabalhador. - Simon Neto, Cláudia Maria (Universidade Federal de São Carlos, 2003)
This research has as its aim to investigate an enterprise program to give instruction to workers during the 90 s in the context of the new organization forms of the process of production and work which characterizes the integrated and flexible enterprise. It tries to identify the workers discourse, motivation, objectives, and the results in the school education. In this perspective it tries to answer the following questions; does this specific modality of school education contribute to the formation of a more critical subject when it increases the possibilities of comprehension and of contraposition to the numberless forms of exploitation and of control in the capitalistic society or does it in a one-sided form cooperate to the workers adjustment and integration to the productive and social reality ? This research begins with the hypothesis that the process of the workers instruction is developed in a complex and contradictory form because education is not limited to the restricted interests of the capital, to the dimension of adjustment of these individuals to the productive process and to the social dynamics, but it also allows a reasoning which is more critical and less identified to the dominating system. Beginning with a questionnaire and a half-structured interview, data have been collected. These instruments have been made to workers who shared a program of instruction developed in a transnational enterprise located in Valinhos-SP, Brazil. Its analysis makes possible to verify the prevalence of the functionality of education to the capital, as this school knowledge makes it easy to benefit the workers performance in the productive activity as well as in the technical and behavioral training courses. On the other side the analysis allows to detect some elements which indicate the contribution of education to forming a more critical subjectivity. The conclusion of this research is that considering the instrumentalization of the formative processes which are dominant in the late capitalism it becomes extraordinarily necessary to develop an education founded in the affirmation of the subject s autonomy, a greater emphasis into the moments which potentially let us see an emancipatory education.
Keywords: Educação; Trabalho; Formação humana; Educação e integração do indivíduo; Educação e autonomia do sujeito; CIENCIAS HUMANAS::EDUCACAO